Spots Archives, April 1978 to November 1978 (1978)
Recorded 04/12/78 [00:02:54] KCPR T-shirt design contest ad [00:03:50] KCPR T-shirt design contest ad [00:05:04] KCPR T-shirt design contest ad [00:05:40] Pablo Cruise Poster Giveaway [00:06:05] Pablo Cruise Giveaway [00:06:24] ASI concert - Pablo Cruise [00:07:38] Concert Promo - Pablo Cruise [00:08:55] "Talk to the Management Phase II" [00:09:28] Health Center, Alcohol Use and Abuse - Shakespeare [00:10:05] Health Center, Alcohol Use and Abuse - Newton Brothers [00:10:52] Health Center, Alcohol Use and Abuse - supermarket [00:11:34] Headeast Promo Recorded 05/21/78 [00:12:42] Weird Al Promo [songs about money?] Recorded 06/10/78 [00:14:46] KCPR Newsday Promo [Vivi St. Amand] [00:15:15] An Hour with Jackson Brown [Jay Birks] [00:15:46] History of KCPR Promo [Frank Calabrese] [00:16:58] SLO Family Services Ad/Promo[Mark T] [00:17:33] KCPR Thank You Promo [Russ Sharer] Recorded 09/09/78 [00:18:06] ASI Concerts - Cheap Trick [Al Yankovic] [00:19:39] ASI Concerts - Cheap Trick [Chuck LASTNAME] [00:21:35] KCPR Thank You Promo [00:22:09] Freedom to Be Foundation Promo - Curlian(?) Photography [Jay Birks] [00:23:02] Oldies Show [Al Booth] [00:24:36] "Is Coming" Promo [00:25:16] KCPR Summer Goodbye [Russ Sharer] [00:25:53] Oldies Show Promo[Al Booth] [00:26:43] "Birks Sicko Music Promo," Anti-Commercial Radio [Jay Birks?] Recorded 10/03/78 [00:27:29] KCPR Giveaway Promo [Chuck] [00:27:56] KCPR Boosters Dance Promo [Franklin Thomas] [00:29:20] Pablo Cruise Not Legal ID [00:29:44] SLO Family Service Center [Mark Trollen] [00:30:22] ECO SLO Promo [Debby Silk and Weird Al] [00:31:42] ASI speakers forum [Franklin Thomas] [00:32:22] KCPR Promo "The Good Sound in SLO Town"[Franklin Thomas] Recorded 10/08/78 [00:32:12] Yosemite Hall Dance [Dana Rice] [00:33:39] ASI Special Events - Pres. Hall Jazz Band Promo [Franklin Thomas?] cut off [00:34:20] Weird Al Promo, [Weird Al] [00:35:42] Weird Al Promo (Gary Gilmore) [Weird Al] [time needed] Open Channel Promo Recorded 10/14/78 [00:37:14] Orchesis [Jerry Peak] [00:37:52] An Hour With [Jay Birks] [00:38:48] KCPR Boosters Promo, Selling Shirts [Franklin Thomas] [00:39:38] KCPR 91 Entertainment Promo [Chuck S] [00:40:15] Cal Poly ASI [Cathy Speanak] [00:41:11] West Coast Education and Research Center [Franklin Thomas] [00:41:52] Society of Wizards and Warriors [Tim Tomastik(?)] Recorded 10/28/78 [00:42:47] Poly Phase Club Promo [Franklin Thomas] [00:43:23] Intramural Department (Field Hockey Promo) [John Z.] [00:44:00] ASI TV Programming/Films [Grant Easton and Franklin Thomas] [00:46:46] ASI Concerts - Pablo Cruise Promo [Chuck S.] [00:46:12] Cal Poly Test Office - English Placement Test [Matt Graham and Cliff Flyum] Recorded 11/05/78 (cut off) [00:47:27] Haunted Hall Party Muir Hall [00:48:06] Cal Poly Extension [Mark T] [00:48:48] Poly Phase - Rock Dance [Bill Simmons] [00:49:44] SLO County Symphony (Gary Carr?) [Weird Al] Recorded 11/19/78 [00:50:50] Homecoming Committee Parade, Get Smart Parody [Matt Graham and Cliff Flyum] [00:52:07] Cal Poly Extension - State Planning Course, Star Trek Parody [Matt Graham and Cliff Flyum] [00:53:04] Homecoming Parade Promo [Macho Mike] [00:53:39] Society of Manufacturing Engineers [Grant Easton and Clark Behnice(?)] [00:54:42] Intercollegiate Rodeo [Phil Manno] [00:55:13] Drug Abuse Promo [Tim Tomastik(?) and Franklin Thomas] [00:56:10] Recreation Administration - Amateur Night[Mark Troeller]